Pancer: A Music Interpretation of the Chronicle of Panjer | Pancer: Sebuah Musik Interpretasi Babad Panjer - I Gusti Agung Kresna Bayu Kepakisan; I Ketut Sudhana (GHURNITA: Jurnal Seni Karawitan, 2023)
This article discusses the percussion of the "Pancer" pepanggulan, which is an interpretation of the certia of the origin of the Panjer traditional village. Pancer is another word for panjer which is the name of a village located in south Denpasar. Pancer means to stick, where what is meant in this case is sticking a spear. Panjer traditional village story, then implemented into a percussion creation pepanggulan with gamelan gong kebyar media entitled "Pancer". The writing of this article aims to provide information about how the shape and description of the composition of the "Pancer" percussion creations pepanggulan, where it is expected to be a motivation and reference in the cultivation of perpanggulan percussion creations in the future. In cultivating the creation of the "Pancer" percussion, the stylist uses the creation method from Alma M. Hawkins including the exploration stage, the improvisation stage and the formation stage. The results obtained are the formation of the full "Pancer" pepanggulan percussion which consists of three parts including the pengawit section which is a final part of the work, the crew section which describes the love story of a king, and the pusher section which describes the king's journey in performing prayers, which in this journey is also the origin of the founding of the traditional village of Panjer.